THE STATE OF KNOWLEDGE IN PUBLIC HEALTH: EPISTEMOLOGICAL REFLECTION - Machado dos Santos , Adelcio; Tenconi, Daniel (Health and Society, 2025)
This article presents an epistemological reflection on the state of knowledge in Public Health, articulating classical theoretical foundations and contemporary contributions to understand the paradigms that structure the field. The analysis begins with a historical overview of the development of Public Health, from the predominance of the biomedical model to the incorporation of interdisciplinary approaches and the social determination of health. This qualitative and exploratory research was based on a systematic literature review and critical analysis of national and international scientific publications, following Brazilian ABNT standards. The study identifies trends in scientific production, highlighting the growth of quantitative and epidemiological research, as well as the gradual appreciation of qualitative methods and community knowledge. It argues that the advancement of Public Health requires ongoing dialogue between different epistemological frameworks, integration between science and public policies, and the enhancement of knowledge translation into social practice. It concludes that understanding epistemological foundations is essential for guiding research, management, and policy-making that effectively and equitably address contemporary health challenges.